Achieving and Maintaining Effective Plasma Concentration of Lithium After Oral Administration - D. G. Makarevich; O. A. Grebenchikov; M. Ya. Yadgarov; L. B. Berikashvili; K. K. Kadantseva; V. V. Likhvantsev (Общая реаниматология)
The aim of the study. To study the achievability and contingency to maintain an effective plasma lithium concentration in the perioperative period in patients undergoing carotid endarterectomy (CEAE) with oral intake of lithium carbonate pills.Materials and methods. It was a prospective study, as a preparatory stage of the multicenter «BINOS» (NCT05126238) RCT. The sample included 15 patients undergoing elective CEAE. In the course of this study, patients were administered oral lithium carbonate, 900 mg per day during 4 perioperative days: two days before the procedure, in the day of surgery and in the 1st postoperative day. Plasma lithium concentration was monitored every 24 hours during all 4 days from the onset of treatment.Results. Increased plasma lithium concentrations were found in blood samples taken at 48 hours (0.68 mmol/l [0.53–0.84, P = 0.004) and 72 hours (0.68 mmol/l [0.62–0.90, P < 0.001), as compared with the initial values (0.14 mmol/l [0.11–0.17).While during the period between 48 and 72 hours from the onset of treatment the plasma lithium concentration remained in the therapeutic range (0.4–1.2 mmol/l) in 100% of patients.Conclusion. Oral intake of lithium carbonate pills at a dose of 900 mg/day during 2 preoperative days provided an effective and safe plasma lithium concentration in 100% of patients enrolled in the study.